ANALISIS POLA PEMBELIAN KONSUMEN MENGGUNAKAN ALGORITMA APRIORI PADA TOKO BERKAH MART - NADA, BELLA KOJAYA; Ridho, Muhammat Rasid (Computer Science and Industrial Engineering, 2021)
Berkah Mart store is a company engaged in the sale of staples in the city of Batam. The Berkah Mart store sells various types of products so that every day the Berkah Mart Store makes a lot of transactions, the transaction data that occur are not managed properly so that data accumulation occurs in the database. One of the ways to take advantage of the accumulated data is by processing the data using a priori algorithm calculation technique which is part of data mining techniques. The a priori algorithm is expected to help Toko Berkah Mart to determine products that are often sold simultaneously and determine the placement of goods according to consumer habits. The results of the a priori algorithm calculation are supported by the use of the tanagra application. One of the algorithm techniques used is high frequency pattern analysis where in this study all rules have a value 10% support and 100% confidence increase in sales.